Metaphor in Psychotherapy - Nergis Lapsekili; Zekeriya Yelboða (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
A metaphor is a figüre of speech in which a word or phrase is applied to an object or an action that it does not literally denote in order to imply a resemblence. Metaphor has been an essential feature of human communication from time immemorial: fairy tales, parables, provers are all examples of metaphor. Human beings regularly use metaphors to communicate with each other, so it is reasonable to expect this figüre of speech to have a place in the process of communication we call psychotherapy. As well as carefully planned and developed majör metaphoric stories to achieve specific therapeutic goals, anectodes, similes, analogies, parables and other brief metaphorical statements, relationship metaphors, tasks with metaphorical meanings, objects can be used with their metaphorican meaning in psychotherapy. Stories when properly constucted and told, are usually more interesting than straight expositions of the points one wishws to make. Of course it is possible to construct boring stories or to tell good stories in a boring way. But well thought out and well narrated stories, told in the right context ca inspire people to undertake tasks and think about things they would not have considered before. Stories, because they deal indirectly with issues and have meanings that are in varying degrees veiled, tend to be less threatening and confronting than direct statements. Listeners are free to take stories at their face value, if their implicit meaning is unacceptable to them at the time. And this result will not damage the existing therapist-client rapport. Suggesting solutions to problems, helping people to recognize themselves, increasing motivation, reframing and redefining problems, reminding subjects of their own resources are all the benefits of clinical uses of metaphors in psychotherapy. In this text, the description of metaphor and usage of metaphor in psychotherapy will be reviewed with samples. [JCBPR 2014; 3(2.000): 116-125]